Stromal Versican Regulates Tumor Growth by Promoting Angiogenesis - Asano, Keiichi; Nelson, Courtney M.; Nandadasa, Sumeda; Aramaki-Hattori, Noriko; Lindner, Daniel J.; Alban, Tyler; Inagaki, Junko; Ohtsuki, Takashi; Oohashi, Toshitaka; Apte, Suneel S.; Hirohata, Satoshi (Scientific reports, 2017)
The proteoglycan versican is implicated in growth and metastases of several cancers. Here we investigated a potential contribution of stromal versican to tumor growth and angiogenesis. We initially determined versican expression by several cancer cell lines. Among these, MDA-MB231 and B16F10 had none to minimal expression in contrast to Lewis lung carcinoma (LLC). Notably, tumors arising from these cell lines had higher versican levels than the cell lines themselves suggesting a contribution from the host-derived tumor stroma. In LLC-derived tumors, both the tumor and stroma expressed versican at high levels. Thus, tumor stroma can make a significant contribution to tumor versican content. Versican localized preferentially to the vicinity of tumor vasculature and macrophages in the tumor. However, an ADAMTS protease-generated versican fragment uniquely localized to vascular endothelium. To specifically determine the impact of host/stroma-derived versican we therefore compared growth of tumors from B16F10 cells, which produced littleversican, in Vcan hdf/ + mice and wild-type littermates. Tumors in Vcan hdf/ + mice had reduced growth with a lower capillary density and accumulation of capillaries at the tumor periphery. These findings illustrate the variability of tumor cell line expression of versican, and demonstrate that versican is consistently contributed by the stromal tissue, where it contributes to tumor angiogenesis.